Food Chemical Quality Assessment : Food and Beverages Products Case Study in Malang City - Mika Vernicia Humairo; Alfian Ihza Mahendra; Caroline Renee Lesmana P; Jihan Alfin Salsabilla; Nadya Nurhikmah; Yudha Eka Pratama (Pusat Publikasi Ilmiah, STKIP Taman Siswa Bima, 2025)
Food safety is the urgency behind testing preservatives, colorants, and sweeteners in snacks and measuring heavy metal levels in marine animals in maintaining public health and ensuring the quality of food consumed. The purpose of conducting food quality testing practicum is to determine the presence or absence of harmful additives that have an impact on health. This research is a descriptive study using a qualitative method using a reagent test kit for the substances to be tested. The results obtained were 5 food samples containing formalin and 1 beverage sample containing cyclamate. In addition to the hazardous food additives test, heavy metal content tests were also conducted on marine animals. The results showed that 6 samples contained lead and 2 food samples contained mercury. All ingredients or substances tested in this study, namely Borax, Formalin, Arsenic (As), Rodhamin B, Methyl Yellow, Saccharin, Cyclamate, Aspartame, Lead (Pb), and Mercury (Hg) are substances that are harmful to health especially if consumed in excessive amounts. Findings from the study indicate that there are still food producers who use hazardous food additives such as preservatives, dyes, and sweeteners in snacks. In addition to food additives, food safety can also be affected by the environment, such as the heavy metal content in seafood